(untitled) (Journal of Hama University, 2022)
This study aimed to identify the impact of strategic leadership in activating the administrative creativity of employees at Apamea Pharmaceutical Industries, where the study focused on the dimensions of strategic leadership: the administrative dimension, the transformational dimension, the political dimension, and the ethical dimension of the strategic leader. The researcher adopted the descriptive analytical method in conducting this study, and used the quantitative method using a questionnaire dedicated to this study, in order to measure the research variables. To derive the results, a study was conducted on Apamia Pharmaceutical Industries in Hama Governorate, with a size of (50) individual department managers and their deputies. The study showed that the employees of Apamea Pharmaceutical Industries in Hama governorate have strategic leadership capabilities to a relatively high degree, and the effects of these trends are evident in light of the difficult conditions experienced by the country and private and public companies. Apamea Pharmaceutical Industries also has a relatively high degree of creative and cognitive capabilities, as well as a significant and positive correlation between strategic leadership in its dimensions and the administrative creativity of the employees of Apamea Pharmaceutical Industries. Among the proposals, we mention: Strengthening the strategic management leadership of the employees of Apamea Pharmaceutical Industries, with crystallizing the process of administrative creativity, embodying and consolidating it among the employees through seminars and conferences in which employees participate in a strategic and deep extent that enables creativity and excellence for the company. Finally, the study presented a set of axes that subsequent studies can work on and research on.